Regional Security Complex Analysis in Australia, United Kingdom, and United States (AUKUS) Viewpoint to the Rivalry between United States and China in Taiwan - Gumantiara, Miftah Ichwani; Haqqi, Halifa; Murdani, Andika Drajat (PT FORMOSA CENDEKIA GLOBAL, 2024)
AUKUS is a trilateral defense pact between Australia, United Kingdom, and United States formed in September 2021. Derived from the countries’ initials, AUKUS serves a security partnership to strengthen integrated deterrence. The pact focuses on enhancing nuclear-powered submarines and developing trilateral cooperation on emerging technology. This study’s discussion focuses on regional security complex analysis in AUKUS viewpoint to the rivalry between United States and China in Taiwan. The method used descriptive research with qualitative approach analysis. Tension between these two countries is seen as a manifestation of their respective national interests. The resolution of the regional security complex here can be observed through the strategies prepared to deter China and how AUKUS could achieve advantages regarding Taiwan's status